Full arterial coronary bypass grafting in dextrocardia with situs inversus totalis: a case report - Aydemir, Numan Ali; Bilal, Mehmet Salih; Yıldız, Yahya; Cine, Nihat; Turhan, Fikret (Cerrahpaşa Medical Journal, 2014)
Although situs inversus totalis is a rare condition, incidence of coronary artery disease in patients having this malposition is similar to that of general population. Among those who are referred to coronary surgery as a result of ischemic heart disease, good surgical results are obtained with minor technical alterations whether the heart’s position itself affects the choice of the grafts. We will present a 55-year-old male patient with dextrocardia and situs inversus who underwent a successful triple coronary bypass grafting procedure with right internal thoracic artery and radial artery grafts.